A Preliminary Investigation of Stimulus Control Training for Worry: Effects on Anxiety and Insomnia. (January 2013) - McGowan, Sarah Kate; Behar, Evelyn
For individuals with generalized anxiety disorder, worry becomes associated with numerous aspects of life (e.g., time of day, specific stimuli, environmental cues) and is thus under poor discriminative stimulus control (SC). In addition, excessive worry is associated with anxiety, depressed mood, and sleep difficulties. This investigation sought to provide preliminary evidence for the efficacy of SC procedures in reducing anxiety-, mood-, and sleep-related symptoms. A total of 53 participants with high trait worry were randomly assigned to receive 2 weeks of either SC training (consisting of a 30-min time- and place-restricted worry period each day) or a control condition called focused worry (FW; consisting of instructions to not avoid naturally occurring worry so that worry and anxiety would not paradoxically increase). At post-training, SC was superior to FW in producing reductions on measures of worry, anxiety, negative affect, and insomnia, but not on measures of depression or positive affect. Moreover, SC was superior to FW in producing clinically significant change on measures of worry and anxiety. Results provide preliminary support for the use of SC training techniques in larger treatment packages for individuals who experience high levels of worry.